Peningkatan Hasil Belajar Siswa Pada Materi Salat Menggunakan Media Ular Tangga Digital - Ameliasari, Elsi; Fahyuni, Eni Fariyatul (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan, 2024)
The problem examined in this study is due to the learning outcomes of students who have not reached school standards related to prayer material. To increase student engagement in the classroom, this study introduces the use of fun and attention-grabbing digital snakes and ladders media. This media is based on one of the traditional games favored by children. This study aims to evaluate changes in students' learning outcomes on the topic of prayer in accordance with Islamic law before and after the application of digital snakes and ladders game media during PAI lessons. This research implements Classroom Action Research (PTK) implemented at SD Hang Tuah 9 with the subject of 16 students of class III-B. Data collection includes interviews with third grade PAI teachers, observation sheets, tests, and documentation. The results of the study were that in the pre-cycle the students' learning outcomes were obtained with an average of 61, then increased in cycle I, namely 75.38, because it had not met the target of the minimum criteria completeness value set by the school (76), so it was continued to cycle II which obtained a KKM score of 95.15. This indicates that digital snakes and ladders media can improve student learning outcomes.